Comparative Study of the Kinetics and Mechanism of Solid- Solid Reaction of HgClI with Cu2HgI4 and Ag2HgI4 - Ahmad, Afaq; Beg, Saba; Varshney, Pooja (Asian Journal of Chemistry, 2010)
The reactions of HgClI with Cu2HgI4 and Ag2HgI4 in the solid state were studied by X-ray diffraction, chemical analysis and electrical resistivity measurements. The kinetics of the reactions has been studied by the moving boundary method. The data for the lateral diffusion best fit the equation xn = kt. The activation energies for the reaction of HgClI with Cu2HgI4 and Ag2HgI4 is 64.38 ± 2.54 J/mol and 96.630 ± 0.183 J/mol, respectively. Both the reactions are diffusion controlled and proceed via vapour phase diffusion of the HgClI.